2005
DOI: 10.1073/pnas.0407768102
|View full text |Cite
|
Sign up to set email alerts
|

Study of the high-potential iron sulfur protein in Halorhodospira halophila confirms that it is distinct from cytochrome c as electron carrier

Abstract: The role of high-potential iron sulfur protein (HiPIP) in donating electrons to the photosynthetic reaction center in the halophilic ␥-proteobacterium Halorhodospira halophila was studied by EPR and time-resolved optical spectroscopy. A tight complex between HiPIP and the reaction center was observed. The EPR spectrum of HiPIP in this complex was drastically different from that of the purified protein and provides an analytical tool for the detection and characterization of the complexed form in samples rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The redox midpoint potential of the P/P ϩ couple therefore is a key parameter indicative for the operating redox range of the whole chain. This E m value of P was determined by equilibrium optical redox titrations on isolated RCs and on membranes as well as through the redox potential dependence of the flash-induced absorption changes in membranes as described previously (13). All these experiments yielded the same result of E m7.5 ϭ ϩ270 Ϯ 10 mV [see Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The redox midpoint potential of the P/P ϩ couple therefore is a key parameter indicative for the operating redox range of the whole chain. This E m value of P was determined by equilibrium optical redox titrations on isolated RCs and on membranes as well as through the redox potential dependence of the flash-induced absorption changes in membranes as described previously (13). All these experiments yielded the same result of E m7.5 ϭ ϩ270 Ϯ 10 mV [see Fig.…”
Section: Resultsmentioning
confidence: 78%
“…In H. halophila, this electron carrier is a high-potential iron sulfur protein (HiPIP) (13). The redox potential of this HiPIP [E m ϭ ϩ165 mV (13)] turned out to be substantially lower than that of other purple bacterial HiPIPs (14) and instead falls within the range of potentials generally observed for electron donors to RCs in phototrophs using MK as pool quinone (15). Because no purple bacterium operating its photosynthetic chain on MK has been described thus far, this finding is surprising.…”
Section: Resultsmentioning
confidence: 99%
“…872 However, other studies have shown a role for HiPIPs distinct from that of cytochrome c . 881 HiPIPs are also found in the membrane of some thermophilic organisms. 879 HiPIPs are mainly found in organisms with a photosynthetic reaction center having a tetraheme cytochrome (THC) subunit.…”
Section: Fe–s Redox Centers In Electron Transfer Processesmentioning
confidence: 99%
“…Many bacteria contain both small cytochromes and HiPIPs and sometimes contain multiple copies of each, a redundancy that has yet to be fully explained. Biophysical studies have shown that, in at least some of the organisms containing a HiPIP and a small cytochrome, both are capable of reducing the reaction center (5)(6)(7)(8). Under a given condition, a single protein (either the HiPIP or the cytochrome) generally appears to be the dominant electron donor (6).…”
mentioning
confidence: 99%